2018
DOI: 10.1111/famp.12388
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parents in Emerging Adults’ Psychological Well‐Being: A Person‐Oriented Approach

Abstract: The purpose of this study was to gain an overview of Spanish emerging adults' family relationships and their link with psychological well-being and psychological distress. The sample comprised 1502 undergraduate students (903 women and 599 men) aged between 18 and 29 (M = 20.32 and SD = 2.13), recruited from two universities in Spain. A cluster analysis identified three groups of families based on the centrality of five family variables: parental involvement, parental support for autonomy, parental warmth, beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 75 publications
(99 reference statements)
10
35
1
Order By: Relevance
“…Although some parents may be perceived in a negative way when they exert high levels of control over their older children (García‐Mendoza, Sánchez‐Queija & Parra, ; Liga, Ingoglia, Liga et al , 2; Wagner & Abaied, ), in general, emerging adults report positive perceptions of their family relationships (Crocetti & Meeus, ; García‐Mendoza, Parra & Sánchez‐Queija, ; Milevsky, Thudium & Guldin, ), which are characterized by affection and a high degree of parental involvement (Duchesne, Ratelle, Larose & Guay, ; Gomez & McLaren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some parents may be perceived in a negative way when they exert high levels of control over their older children (García‐Mendoza, Sánchez‐Queija & Parra, ; Liga, Ingoglia, Liga et al , 2; Wagner & Abaied, ), in general, emerging adults report positive perceptions of their family relationships (Crocetti & Meeus, ; García‐Mendoza, Parra & Sánchez‐Queija, ; Milevsky, Thudium & Guldin, ), which are characterized by affection and a high degree of parental involvement (Duchesne, Ratelle, Larose & Guay, ; Gomez & McLaren, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study, therefore, confirms that, in addition to psychological control, behavioural control by families is also related to unhealthy romantic relationships during emerging adulthood. These results highlight, once again, the negative role played by parental control (particularly behavioural control, for which less evidence exists) during emerging adulthood [40, 41].…”
Section: Discussionmentioning
confidence: 91%
“…Behavioural control, characterised by the establishment of limits and the supervision of children's behaviour [40], has been shown to be necessary and healthy during adolescence [34]. However, although few studies have focused on this particular issue, behavioural control seems to be a negative variable during emerging adulthood, since it hampers young people's development during this period [41, 42] and may also interfere with the establishment of healthy romantic relationships. Whatever the case, exploring the relationship between behavioural control during emerging adulthood and romantic attachment is particularly important due to the scarcity of extant research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…As children reach emerging adulthood, their relationship with their parents needs to change in order to adjust to the fact that although due to their socioeconomic situation they are still fairly dependent on their parents, they are nevertheless mature adults at many levels [28,29]. Secondly, it is important to take families into account because research has shown that this context continues to play a fundamental role in young peoples’ development, even during the third decade of their lives [66,67,68]. The present study aims to shed some light on family relations during this period among two samples of university students in Spain and Portugal by analyzing parenting styles and their implications for emerging adults’ psychological wellbeing and adjustment, with a special focus on sex differences.…”
Section: Discussionmentioning
confidence: 99%